Сасо-2 INTESTINAL PERMEABILITY AND Pgp-AFFINITY OF PHOSPHAZIDE - D. Yu. Grebenkin; Ya. M. Stanishevskiy; I. E. Shohin; A. M. Stoinova; M. A. Karpova; A. G. Koryakova; A. V. Ryabova; B. V. Brovchenko; A. A. Smirnov (Разработка и регистрация лекарственных средств)
In this work the intestinal permeability of phospazide in vitro was investigated using Caco-2 cell model in apical-basolateral (A-B) and basolateral-apical (B-A) directions as well as with the option of adding of P-glycoprotein (Pgp) inhibitor cyclosporine A. The following standard substances were used: ranitidine and propranolol. Papp values of test and standard substances were obtained. The obtained data were compared with the values (A) log P for the test and standard substances. According the results of this study, the phosphatide presumably has a low intestinal permeability in terms of BCS. The affinity of phosphazide for the efflux transporter Pgp was demonstrated.